(untitled) (Revista de Ciências Agroveterinárias, 2022)
Potato (Solanum tuberosum L.) is one of the main crops in the Andean region and due to environmental aspects, the use of biocontrol agents is considered a safe way to produce potato seed tubers.The objective of the study was to evaluate potato inoculation with Trichoderma sp. as a matrix and rhizobacteria Bacillus simplex and Azotobacter sp. on the growth of potato seedlings from in vitro culture, for the production of seed tubers in a greenhouse. The inoculation of microorganisms was carried out in pots, using five potato genotypes for processing. The inoculation treatments were: control, Trichoderma sp., Trichoderma sp. + Azotobacter sp., Trichoderma sp. + Bacillus simplex, Trichoderma sp. + B. simplex + Azotobacter sp. The potato genotypes were cv. Unica (CIP392797.22), cv. Bicentenaria, the advanced clones CIP 396311.1, CIP 399101.1, and the experimental clone UH-09 from the Universidad Nacional José Faustino Sánchez Carrión. A completely randomized design was used, under a factorial arrangement and comparisons between treatments were made at p<0.05. All inoculant treatments exceeded the control in number and weight of tubers per plant as well as in tuber size. Inoculations of Trichoderma sp. alone or with Azotobacter sp. increased plant height, number of leaves per plant and vegetative uniformity; inoculations with the Trichoderma sp. + B. simplex + Azotobacter sp. consortium, improved the dry weight of the foliage, number of shoots per plant and vegetative vigor. There were significant interactions between potato genotypes and inoculant treatments for plant uniformity, vegetative vigor, and the foliage’s dry weight. Coinoculation with Trichoderma sp. and some bacterial strains promote the growth of in vitro potato seedlings, increasing the size and weight of the seed tubers and plant biomass, indicating an interrelation between fungi and bacteria that influence the production of potatoes in a greenhouse.